Prevention of Sepsis in Children: A New Paradigm for Public Policy - Carley Riley; Derek S. Wheeler (Critical Care Research and Practice)
Sepsis is one of the leading causes of death worldwide. While the management of critically ill patients with sepsis is certainly better now compared to 20 years ago, sepsis-associated mortality remains unacceptably high. Annual deaths from sepsis in both children and adults far surpass the number of deaths from acute myocardial infarction (AMI), stroke, or cancer. Given the substantial toll that sepsis takes worldwide, prevention of sepsis remains a global priority. Multiple effective prevention strategies exist. Antibiotic prophylaxis, immunizations, and healthcare quality improvement initiatives are important means through which we may reduce the morbidity and mortality from sepsis around the world. Inclusion of these strategies in a coordinated and thoughtful campaign to reduce the global burden of sepsis is necessary for the improvement of pediatric health worldwide.